Case report: Isolated oligometastatic disease of the prostate from a primary lung adenocarcinoma - Kamel, Josette M.; Arjani, Simran; Fedorov, Kateryna; Sapna, Fnu; Cheng, Jinrong; Mantzaris, Ioannis (Frontiers in Oncology, 2024)
Secondary prostate cancer typically occurs from direct seeding of a renal or bladder tumor. Metastasis via hematogenous spread is exceedingly rare and is typically identified incidentally at autopsy. This report describes a 72-year-old male with lung adenocarcinoma initially staged as Stage IA2 who developed oligometastatic disease of the prostate. He was initially treated with radiation therapy and was found to have a hypermetabolic focus in the prostate gland during surveillance PET/CT imaging 6 months following treatment.Subsequent biopsy revealed metastatic lung adenocarcinoma in 6/6 core samples, leading to diagnosis of oligometastatic disease of the prostate. To our knowledge, this is the first report of isolated oligometastatic disease to the prostate from a primary lung adenocarcinoma.